Analysis of the Sarbanes-Oxley Ban on Non-Audit Services From an Auction Model Perspective. (July 2021) - Elitzur, Ramy; Gavious, Arieh; Minchuk, Yizhaq
This study analyzes the impact of the Sarbanes-Oxley Act's (SOX) ban on providing both auditing and nonaudit services by auditors to their clients. We use a first-price private value auction to compare a setting in which auditors can compete for both audit and nonaudit services with an auction in which they can compete for only one of the two services. Consistent with empirical studies, we show that the ban on nonaudit services results in fee hikes for both audit and nonaudit services, as the number of bidders (audit firms) is smaller in the post-SOX setting relative to pre-SOX setting in both auctions. Consequently, we demonstrate that, after the ban, payoffs have increased for audit firms and decreased for their clients, due to the increase in both audit and nonaudit services fees. Finally, we show that increasing the penalty for an audit failure, contrary to common wisdom, results in improved payoffs for audit firms.